2011
DOI: 10.1183/09031936.00194710
|View full text |Cite
|
Sign up to set email alerts
|

E-cadherin gene polymorphisms in asthma patients using inhaled corticosteroids

Abstract: E-cadherins form intercellular junctions that maintain epithelial integrity. Epithelial integrity is impaired in asthma and can be restored by inhaled corticosteroids (ICSs). Our aim was to investigate the association of CDH1 gene polymorphisms (single-nucleotide polymorphisms (SNPs)) with airway remodelling, inflammation and forced expiratory volume in 1 s (FEV1) decline in asthma patients and assess whether ICSs modulate these effects.Bronchial biopsies of 138 asthmatics were available (population 1). Associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 36 publications
(43 reference statements)
1
28
0
Order By: Relevance
“…TH2 inflammation appears to be a potent modulator of epithelial permeability, not only in the gut, but also the skin, nasal epithelium, and 16HBE cells (9, 11, 12). In the context of asthma, previous studies have reported decreased expression levels of certain junctional proteins, including epithelial cadherin, occludin and ZO-1 (8, 3436). Prior work has also shown that innate immune mediators such as TNF-alpha can influence claudin expression in airway epithelial cells (18).…”
Section: Discussionmentioning
confidence: 97%
“…TH2 inflammation appears to be a potent modulator of epithelial permeability, not only in the gut, but also the skin, nasal epithelium, and 16HBE cells (9, 11, 12). In the context of asthma, previous studies have reported decreased expression levels of certain junctional proteins, including epithelial cadherin, occludin and ZO-1 (8, 3436). Prior work has also shown that innate immune mediators such as TNF-alpha can influence claudin expression in airway epithelial cells (18).…”
Section: Discussionmentioning
confidence: 97%
“…The CDH1 rs16958383 has been found to have a borderline association with breast cancer in premenopausal, but not postmenopausal, women [25]. Recently, Ierodiakonou et al [26] showed that rs7186053, rs4783573 and rs16958383 may contribute to airway remodeling and lung function in asthma patients using inhaled corticosteroids, however their impact on pulmonary cancer has yet to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…This study could not address the issue of the effect of CS on remodeling in NFE biopsied group. Other studies have yielded contradictory results [18, 19]. Thermoplasty and novel targeted therapies may prove much more beneficial against remodeling [20, 21].…”
Section: Discussionmentioning
confidence: 99%